Penguatan Hubungan Indonesia Dan Palestina Perspektif Pembukaan Undang-Undang Dasar Negara Republik Indonesia Tahun 1945 Dan Siyasah Dauliyah - Mey Adriesti; Frenki; Mu'in, Fathul Mu'in (IAI Darussalam, 2025)
This study aims to analyze the relationship between Indonesia and Palestine from the perspective of the Preamble to the 1945 Constitution of the Republic of Indonesia (UUD 1945) and Siyasah Dauliyah. The Preamble to the 1945 Constitution emphasizes that colonialism must be abolished because it is contrary to the values of humanity and justice. From the perspective of Siyasah Dauliyah (Islamic foreign policy), Indonesia's stance reflects its moral and political obligation to defend oppressed nations. In addition, Indonesia also has an obligation to participate in creating world order based on independence, lasting peace, and social justice. Therefore, Indonesia's support for Palestine can be understood as a form of implementing the constitutional mandate as well as part of Indonesia's foreign policy that consistently rejects all forms of colonialism. The method used in this study is qualitative with a content analysis approach or library research. The data was obtained from the 1945 Constitution, government policies, diplomatic documents, and relevant literature on Indonesia-Palestine relations. The results of the study show that Indonesia's support for Palestine is manifested in various forms, such as recognition of Palestine as an independent state, diplomatic efforts in international forums, and the provision of humanitarian aid. This confirms that Indonesia's support for Palestine is not merely a diplomatic interest, but also a manifestation of national identity and fundamental principles of the state.